Mengeksplorasi Disparitas: Analisis Mendalam Persepsi Mahasiswa Terhadap Efektivitas Evaluasi Pembelajaran Daring Di Era Pandemi Covid-19 - Hermansyah, Hermansyah; Mardhia, Dwi; Yahya, Fahmi; Gunawan, Gunawan; Sahidu, Hairunnisyah (Indonesian Journal of STEM Education, 2022)
The COVID-19 pandemic necessitated a rapid shift from traditional face-to-face learning to online modalities, including student evaluations. This study delves into the disparity between the perceived effectiveness of online learning evaluations and actual student experiences during the pandemic, drawing insights from existing data that highlighted student disagreement regarding the ability of online evaluations to measure material mastery, foster creativity, and enhance thinking skills. While previous research often focuses on quantitative correlations, this qualitative-dominant analysis aims to explore the underlying reasons for student dissatisfaction. It investigates how factors such as technical issues, time pressure, and the design of online assessment tools contribute to these perceptions. By understanding the nuances of student perspectives, this paper seeks to provide valuable insights for educators and policymakers in designing more effective, equitable, and student-centric online evaluation strategies that move beyond mere digital replication of traditional methods.